97.9k views
12 votes
Simplify this problem for me

Simplify this problem for me-example-1

1 Answer

4 votes

Answer:


\displaystyle E=e^(5x)

Explanation:

Exponentials

Properties of exponentials:


x^ax^b=x^(a+b)


(x^a)/(x^b)=x^(a-b)

Simplify:


\displaystyle E=(e^(-2)\cdot e^(2x+3))/(e^(1-3x))

Multiplying in the numerator:


\displaystyle E=(e^(-2+2x+3))/(e^(1-3x))=(e^(+2x+1))/(e^(1-3x))

Applying the quotient:


\displaystyle E=e^(2x+1-(1-3x))

Operating:


\displaystyle E=e^(2x+1-1+3x)

Simplifying:


\boxed{\displaystyle E=e^(5x)}

User Skyp
by
4.5k points